Caracterização da implementação do lean manufacturing na região amazônica : identificação do grau de adoção e seu efeito no desempenho empresarial - Negrão, Léony Luis Lopes (Universidade Federal de São Carlos, 2016)
The objectives of this thesis were to identify the path of implementation of lean practices in the manufacturing industry located in a region of scarce resources from a developing country, to evaluate the insertion degree such means according certain control variables (company size, industrial sector and the main productive typology) as well as to evaluate the effects of the lean manufacturing implementation on the performance of the companies studied. By means of a Survey, it was possible to investigate the lean manufacturing implementation using robust statistical techniques to define the measurement model defined as the mean of lean manufacturing adoption by the industry researched and to evaluate the effect of such adoption on performance. The results show a high, but partial, degree of lean adoption, which is observed by the identification of its implementation path composed of six internal practices (Single-Minute Exchange of Dies, Human Resource Management, Continuous Flow, Total Productive Maintenance, and Statistical Process Control) and two external (Supplier feedback and Customer engagement). Two other important lean practices (Just In Time delivery and Supplier development) have not been implemented, probably due to the region and country characteristics in where the companies are located such as: remote suppliers and lack of transport/logistics infrastructure plus the great territorial extension. In addition, such adoption has occurred in a fragmented way, as from 36 operational measures that comprise the eight practices considered as the lean implementation path, 13 have not been implemented. Moreover, it was verified the degree of adoption of the lean practices changes according to the company’s size (bigger companies tend to incorporate more practices compared to smaller companies) and the industrial sector. However, there has been no variation in the degree of adoption considering the main productive typology. Finally, it was observed the Lean Manufacturing interrelationship model has a positive effect on operational, financial and environmental performances.
Keywords: Sistema de produção enxuta; Manufatura enxuta; Sistema Toyota de produção; Lean production system; Lean manufacturing; Toyota production system; ENGENHARIAS::ENGENHARIA DE PRODUCAO